NEW CONCLUSIONS ON THE RELATIONSHIPS OF THE OPOSSUM-LIKE MARSUPIALS, WHITH AN ANNOTATED CLASSIFICATION OF THE DIDELPHIMORPHIA (Ameghiniana, 2014)
Biochemical, chromosomal, and anatomical characters were considered in an attempt to uncover the phylogenetic relationships of didelphimorphian marsupials. Groupings based on serology were very similar to those obtained by cladistic analysis (both manual and quantitative) of the karyotypes and morphology. Few anatomical characters evolved derived states only once, so that monophyletic groups were defined on polythetic oombinations of non-unique states. Some dubious relations (e.g. of Peratherium with the murine opossums, and of Sparassocynus near Lutreolina) are regarded as examples of convergence through spacial and temporal vicariance. A fundamental dichotomy of the opossum-like marsupials is 1ecognized at the superfamily level; the new taxon Microbiotherioidea is erected to include Microbiotheriidae (with Microbiotheriinae, Glasbiinae, and Pedyomyinae as subfamilies), Stagodontidae, Caroloameghiniidae, and Peradectidae, while tlle Didelphoidea are restricted to comprise only the Didelphidae and Sparassocynidae; Peradectids were probably the progenitors of didelphoids and borhyaenoids, and (albeit at a time preceding probably the microbiotherioid -delphoid divergence), the dasyuroids and all other marsupial groups as well. The possible occurrence of peradectids in Australia and Africa is pointed out. Didelphidae includes three subfamilies, the Herpetotheriinae (Peratherium and allies) being of an earlier origin that the more closely related Caluromyinae and Didelphinae. The latter is further divided into three tribes: Didelphini, Metachirini and Marmosini. The splitting of Marmosa into three different genera, namely Marmosa, Micoureus, and Thylamys, is proposed.